2013
DOI: 10.1007/s00449-013-1058-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous wastewater treatment, electricity generation and biomass production by an immobilized photosynthetic algal microbial fuel cell

Abstract: A photosynthetic algal microbial fuel cell (PAMFC) was constructed by the introduction of immobilized microalgae (Chlorella vulgaris) into the cathode chamber of microbial fuel cells to fulfill electricity generation, biomass production and wastewater treatment. The immobilization conditions, including the concentration of immobilized matrix, initial inoculation concentration and cross-linking time, were investigated both for the growth of C. vulgaris and power generation. It performed the best at 5 % sodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…Other studies reported that immobilized microalgae within alginate beads in microbial fuel cells can enhance power generation. The Coulombic efficiency of the microbial fuel cells with immobilized Chlorella vulgaris in alginate beads could reach 9.40% and 14.1%, respectively 29 , 30 . In the present study, we evaluated the feasibility of using alginate immobilized Chlorella cells coated directly on the ITO anode surface, to enhance bioelectricity generation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that immobilized microalgae within alginate beads in microbial fuel cells can enhance power generation. The Coulombic efficiency of the microbial fuel cells with immobilized Chlorella vulgaris in alginate beads could reach 9.40% and 14.1%, respectively 29 , 30 . In the present study, we evaluated the feasibility of using alginate immobilized Chlorella cells coated directly on the ITO anode surface, to enhance bioelectricity generation.…”
Section: Introductionmentioning
confidence: 99%
“…1) a lag phase where increasing light intensity does not improve performance; 2) a light limiting phase where increasing light intensity improves performance, 3) a light saturating phase where increasing light intensity does not improve performance, and 4) a light inhibition phase, where increasing light intensity decreases performance. For C. vulgaris , a light intensity of 500–6500 lux has been reported to be in optimum range [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cathode is provided with the desired source microbe. After oxidation at the anode protons pass through the PEM to the cathode, where they get reduced into water (He et al, 2014; Figure 1). This is a double-chambered MFC that exists more commonly.…”
Section: Elements Constituting Microbial Fuel Cellsmentioning
confidence: 99%